The influence of dietary vitamin C and E supplementation on the physiological response of pirarucu, Arapaima gigas, in net culture - de Menezes, Glauber Cruz; Tavares-Dias, Marcos; Ono, Eduardo Akifumi; de Andrade, Jaqueline Inês Alves; Brasil, Elenice Martins; Roubach, Rodrigo; Urbinati, Elisabeth Criscuolo [UNESP]; Marcon, Jaydione Luiz; Affonso, Elizabeth Gusmão (Elsevier, 2006)
This study evaluated the efficacy of dietary vitamin C (ascorbic acid or AA), vitamin E (α-tocopherol or α-T), and C + E supplementation on the blood parameters of Arapaima gigas grown in net cages for 45 days. Four treatments were tested: control (commercial feed); C800; E500 and C + E (800 + 500) with supplementation of 800 mg AA kg- 1, 500 mg α-T kg- 1 and 800 + 500 mg AA + α-T kg- 1, respectively. Hematocrit (Ht), red blood cells (RBC), and hemoglobin concentration (Hb) (oxidative status indicators), thrombocytes and leukocytes (immunological indicators), plasma protein and glucose were evaluated. Fish fed vitamin C and C + E supplemented diets showed greater weight gain and survival. Dietary vitamin C and C + E diet supplementation resulted in increased Ht, Hb, RBC, MCHC, total leukocytes, total proteins, thrombocytes and eosinophils compared to the control and α-T. The α-tocopherol-supplemented diet reduced the number of total thrombocytes, lymphocytes and neutrophils and increased glucose and eosinophils relatively to the control. In general, leukocytes and thrombocytes were good indicators of the efficiency of vitamin on the defense mechanism of the A. gigas reared in cages. Results indicate that high α-T diet supplementation provides no benefit for the maintenance of the oxidative or the immunological status of A. gigas. However, it was demonstrated that high dietary AA improves A. gigas immunological status. Red blood cell indices and immune system indicators showed no synergistic effect between the vitamins after supplementing the A. gigas diet with α-T + AA. © 2006 Elsevier Inc. All rights reserved.
Keywords: Ascorbic acid; Culture; Hematology; Leukocytes; Metabolism; Pirarucu; Tocopherol; alpha tocopherol; ascorbic acid; biological marker; animal experiment; aquaculture; arapaima gigas; comparative study; concentration (parameters); controlled study; eosinophil; erythrocyte; evaluation; fish; glucose blood level; hematocrit; hematological parameters; immune system; immunology; leukocyte; nonhuman; oxidation; physiology; pirarucu; plasma; protein blood level; rearing; survival; thrombocyte; vitamin supplementation; weight gain; Animals; Aquaculture; Ascorbic Acid; Blood Glucose; Blood Proteins; Diet; Erythrocyte Count; Erythrocyte Indices; Fishes; Hematocrit; Hemoglobins; Leukocyte Count; Platelet Count; Vitamin E; Arapaima gigas